Challenges of integrating recreational activities into the school programme of the special needs children (2012)
Recreational activity is important and relevant to human development as well as the achievement of optimum health. It has vital role to play in helping special needs children to develop physically, socially and emotionally. Recreational activity could help the children to live a more fulfilling, satisfying and healthy life in the world in which their capability is limited. Although, the special needs children have equal right as the able-bodied persons to participate in leisure time activity, some challenges are standing in the way of special needs schools in providing this opportunity. The desire to find out these constraints informed this study. Descriptive survey research design was used in the study. The one hundred (100) participants used in the study were from five special schools in Ibadan, Oyo State, and Asaba, Delta State using purposive sampling technique. The instrument used was the Recreational Integration Challenge Questionnaire (RICQ) with four subsets and four items in each, which focused on the actual challenges which children with special needs are facing in the implementation of integrating recreational activities into the schools’ programmes. The descriptive statistics of chi-square (x2) was employed to test the hypotheses formulated at 0.05 alpha level. The findings revealed that facilities and equipment, financial constraints, time schedules and adjustment to motor skills learning significantly posed challenges to the integration of recreational activities. The study among other things recommended that private, philanthropists and business tycoons should invest in the construction and provision offunctional facilities and equipment that will motivate the special needs children to participate in recreational activities for health.